CUSTOMER LOYALTY OF TENUN IKAT MSMES: THE ROLE OF BRAND IMAGE, BRAND LOVE, AND CUSTOMER ENGAGEMENT - Fara Shahila; Anita Sumelvia Dewi (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
The purpose of this research is to examine how brand image and brand affinity impact customer retention, while considering consumer engagement as a moderating factor. Positive brand image becomes one of the important factors that can influence customer loyalty levels, while brand love creates strong emotional bonds between consumers and brands. Using quantitative methods, data was collected from 150 respondents who had used specific brands for more than one year. The use of Structural Equation Modeling (SEM) in data analysis revealed connections between various variables. The study findings shed light that a strong brand image greatly impacts customer loyalty, and this bond is further reinforced by brand affection. Additionally, consumer interaction helps regulate the connection between brand affection and customer commitment, as increased engagement enhances the favorable impact of brand affection on loyalty. These findings demonstrate the importance for companies to enhance brand image and build closeness with consumers to drive loyalty.